Tinjauan Teologis Manifestasi Roh Kudus dalam Peristiwa Pentakosta di Azusa Street - Cibro, Yoel Kurniabudi; Ferdianto, Karolin; Abraham, Jessica Elisabeth (Sekolah Tinggi Teologi Kharisma, 2025)
AbstractThe spiritual awakening on Azusa Street in 1906 was a continuation of previous Christian movements and became the starting point for the birth of the modern Pentecostal movement. This research aims to analyze the manifestation of the Holy Spirit, particularly the gift of tongues, and its influence on the development of Pentecostal church theology. The method used is a qualitative study with a historical and theological approach. The results of the study show that glossolalia is seen as the main evidence of the baptism of the Holy Spirit, but it causes differences in views among various Christian traditions. This study emphasizes the importance of a contextual and inclusive understanding in assessing the meaning of the gift of the Holy Spirit for the church today. Keywords: Azusa Street, Holy Spirit, Tongues, Pentecostal Thelogy, Glossolalia AbstrakKebangkitan rohani di Azusa Street tahun 1906 merupakan kelanjutan dari gerakan kekristenan sebelumnya dan menjadi titik awal lahirnya gerakan Pentakosta modern. Penelitian ini bertujuan untuk menganalisis manifestasi Roh Kudus, khususnya karunia bahasa roh, dan pengaruhnya terhadap perkembangan teologi gereja Pentakosta. Metode yang digunakan adalah studi kualitatif dengan pendekatan historis dan teologis. Hasil kajian menunjukkan bahwa glossolalia dipandang sebagai salah satu bukti utama baptisan Roh Kudus, namun menimbulkan perbedaan pandangan di antara berbagai tradisi Kristen. Penelitian ini menekankan pentingnya pemahaman yang kontekstual dan inklusif dalam menilai makna karunia Roh Kudus bagi gereja masa kini. Kata Kunci: Azusa Street, Roh Kudus, Bahasa Roh, Teologi Pentakosta, Glossolalia